2022
DOI: 10.3390/ma15238560
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Melting (SLM) Additively Manufactured CoCrFeNiMn High-Entropy Alloy: Process Optimization, Microscale Mechanical Mechanism, and High-Cycle Fatigue Behavior

Abstract: The equiatomic CoCrFeNiMn high-entropy alloy (HEA) possesses excellent properties including exceptional strength–ductility synergy, high corrosion resistance, and good thermal stability. Selective laser melting (SLM) additive manufacturing facilitates the convenient fabrication of the CoCrFeNiMn HEA parts with complex geometries. Here, the SLM process optimization was conducted to achieve a high relative density of as-built CoCrFeNiMn HEA bulks. The mechanisms of process-induced defects and process control wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…[ 173 ] High‐density nanotwins were also observed after the stress‐controlled fatigue of SLM‐fabricated CrMnFeCoNi HEA. [ 224 ] Apart from fatigue‐induced twinning, the LPBF‐fabricated Fe 40 Mn 20 Co 20 Cr 15 Si 5 HEA also showed fatigue‐induced FCC‐to‐HCP transformation due to low stacking fault energy. The deformation twinning in the transformed HCP phase further enhanced the fatigue limit to 325 MPa in the stress‐controlled fully‐reversed bending fatigue tests.…”
Section: Cyclic Deformationmentioning
confidence: 99%
“…[ 173 ] High‐density nanotwins were also observed after the stress‐controlled fatigue of SLM‐fabricated CrMnFeCoNi HEA. [ 224 ] Apart from fatigue‐induced twinning, the LPBF‐fabricated Fe 40 Mn 20 Co 20 Cr 15 Si 5 HEA also showed fatigue‐induced FCC‐to‐HCP transformation due to low stacking fault energy. The deformation twinning in the transformed HCP phase further enhanced the fatigue limit to 325 MPa in the stress‐controlled fully‐reversed bending fatigue tests.…”
Section: Cyclic Deformationmentioning
confidence: 99%
“…During the fabrication of the multi-material 316L/HEA/NiTi samples via SLM, the HEA alloy was built onto the 316L alloy, followed by the NiTi alloy onto the HEA. HEA samples were successfully obtained via SLM, and the energy density for this alloy was selected on the basis of this study [23]. For 316L and HEA alloys, the SLM parameters were chosen based on energy density according to existing data [24,25].…”
Section: The Slm Process Parametersmentioning
confidence: 99%
“…Zhang et al [27] utilized different screening strategies to optimize the process parameters of CoCrFeNiMn HEA produced by SLM. They observed that increasing laser energy density initially led to higher sample density (up to 98.87%), but further energy increases resulted in decreased density, eventually stabilizing.…”
Section: Introductionmentioning
confidence: 99%